2019
DOI: 10.1111/chd.12786
|View full text |Cite
|
Sign up to set email alerts
|

Stenting the vertical neonatal ductus arteriosus via the percutaneous axillary approach

Abstract: Background/Objective Stenting the ductus arteriosus (DAS) has become an alternative to surgical systemic to pulmonary artery shunts in neonates with ductal‐dependent pulmonary blood flow (PBF). Femoral approach for a vertical ductus can be difficult secondary to the acute angle and tortuous course, thus alternative access sites have been explored. Carotid access complications have been reported in 5%‐10%. The extensive use of an axillary arterial approach in the United States has not been reported. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Although there is a paucity of large-scale data on vascular access for PDA stenting, multiple smaller observational studies present promising outcomes for the carotid and axillary arteries, particularly for approaching vertical PDAs through the superior aspect of the aortic arch. 25,30,[35][36][37][38][39][40][41] Bauser-Heaton et al 36 observed that carotid and axillary artery access is more commonly used in highly tortuous PDAs than the femoral artery and that procedural and late complications were similar regardless of the access site. Similarly, Alsawah et al 37 reported that percutaneous carotid access was more commonly used in complex ductal anatomy, and they found that both immediate access-related complications and delayed local complications in these cases were significantly lower than in cases that used the femoral artery.…”
Section: Vascular Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there is a paucity of large-scale data on vascular access for PDA stenting, multiple smaller observational studies present promising outcomes for the carotid and axillary arteries, particularly for approaching vertical PDAs through the superior aspect of the aortic arch. 25,30,[35][36][37][38][39][40][41] Bauser-Heaton et al 36 observed that carotid and axillary artery access is more commonly used in highly tortuous PDAs than the femoral artery and that procedural and late complications were similar regardless of the access site. Similarly, Alsawah et al 37 reported that percutaneous carotid access was more commonly used in complex ductal anatomy, and they found that both immediate access-related complications and delayed local complications in these cases were significantly lower than in cases that used the femoral artery.…”
Section: Vascular Approachmentioning
confidence: 99%
“…37 Partly in an effort to avoid these potentially devastating neurologic consequences, other interventionists have attempted vertical PDA access through the axillary artery. [38][39][40]42 Although subclavian artery injury is possible with axillary artery access, for many years, classic Blalock-Taussig shunts have sacrificed the subclavian artery with no significant long-term complications. 43 This likely represents the reason that interventionists such as Lee et al 39 prefer the axillary approach.…”
Section: Vascular Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the patients with axillary access developed vascular complications. Several reports have described the axillary approach for PDA stenting and concluded that axillary access provides a safe, direct approach to the PDA, although potential complications can arise particularly pseudoaneurysm formation 10,26–28 . Patients with PDAs originating from the descending aorta, which are accessible via a retrograde approach (i.e., femoral/umbilical), still require care when performing femoral arterial access to avoid femoral artery thrombosis, 9 which occurred in 11% of patients (2/18).…”
Section: Discussionmentioning
confidence: 99%